2006
DOI: 10.1248/bpb.29.830
|View full text |Cite
|
Sign up to set email alerts
|

Anti-complementary Activity of Ursane-Type Triterpenoids from Weigela subsessilis

Abstract: A new ursane-type triterpenoid, weigelic acid (1), and seven known compounds, ursolic acid (2), ilekudinol A (3), corosolic acid (4), ilekudinol B (5), esculentic acid (6), pomolic acid (7), and asiatic acid (8) were isolated from the leaf and stem of Weigela subsessilis. The structure of the new triterpenoid was established as 1b b,2a a,3a a,23-tetrahydroxyurs-12-en-28-oic acid on the basis of spectroscopic analyses. In addition, the isolated compounds were evaluated for their anti-complement activity against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 25 publications
3
19
0
2
Order By: Relevance
“…Corosolic acid has also been isolated from a number of other plant species including but not limited to Vaccinium macrocarpon (cranberry) [4], Ugni molinae [5], Eriobotrya japonica [6–10], Perilla frutescens [11], Weigela subsessilis [12, 13], Glechoma longituba [14], Potentilla chinensis [15], Rubus biflorus [16], and Phlomis umbrosa [17]. Many of these plants are native to Asia, although corosolic acid has also been isolated from European and South American plants.…”
Section: Introductionmentioning
confidence: 99%
“…Corosolic acid has also been isolated from a number of other plant species including but not limited to Vaccinium macrocarpon (cranberry) [4], Ugni molinae [5], Eriobotrya japonica [6–10], Perilla frutescens [11], Weigela subsessilis [12, 13], Glechoma longituba [14], Potentilla chinensis [15], Rubus biflorus [16], and Phlomis umbrosa [17]. Many of these plants are native to Asia, although corosolic acid has also been isolated from European and South American plants.…”
Section: Introductionmentioning
confidence: 99%
“…Although the low density lipoprotein oxidation inhibitory effect and the anticomplementary activity of constituents from W. subsessilis have been investigated (Thuong et al, 2006(Thuong et al, , 2005, the mechanisms underlying the anticancer action of W. subsessilis are not clear. Flavonoids, coumarins and triterpenoids are among the reported constituents from the leaf and fl ower of the edible W. subsessilis (Thuong et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Although the low density lipoprotein oxidation inhibitory effect and the anticomplementary activity of constituents from W. subsessilis have been investigated (Thuong et al, 2006(Thuong et al, , 2005, the mechanisms underlying the anticancer action of W. subsessilis are not clear. Flavonoids, coumarins and triterpenoids are among the reported constituents from the leaf and fl ower of the edible W. subsessilis (Thuong et al, 2006). Corosolic acid (2α-hydroxyursolic acid) is one of the main triterpenoids, and it has been reported that corosolic acid has antitumor properties, such as induction of apoptosis in HeLa cells, and protein kinase C inhibitory activity (Ahn et al, 1998;Xu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…10) Corosolic acid (CRA) is a triterpenoids discovered in many medicinal plants such as Lagerstroemia speciosa (banaba) and Weigela subsessilis. 11,12) CRA displays anti-diabetic activities in some animal experiments and clinical trials, while anti-diabetic drugs can affect cancer in experimental systems and in epidemiological studies. 13,14) CRA also has anti-tumor properties against several human cancer cells, 15,16) but the mechanisms for this anti-cancer activity in HER2 overexpressed gastric cancer have not yet been explored.…”
mentioning
confidence: 99%